2017
DOI: 10.1016/j.fertnstert.2016.12.023
|View full text |Cite
|
Sign up to set email alerts
|

Serum and follicular fluid monocyte chemotactic protein-1 levels are elevated in obese women and are associated with poorer clinical pregnancy rate after in vitro fertilization: a pilot study

Abstract: Elevations in serum and FF MCP-1 levels are positively correlated with adiposity and negatively correlated with pregnancy rates (PRs) in women undergoing IVF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 46 publications
3
39
0
Order By: Relevance
“…We found that the fertilization rate and implantation rate in overweight and obese PCOS patients were not significantly different from those of the normal weight patients. As obesity is a state of chronic inflammation and metabolic disorder, markers of inflammation and oxidative stress are increased in the serum and ovarian follicular fluids (Merhi et al, 2015;Buyuk et al, 2017), which may have a negative impact on the IVF outcomes (Cakiroglu et al, 2016). The aberrant serum metabolic changes, such as the increased cholesterol, triglycerides, and apolipoprotein A, were often observed in obesity, which were usually reflected in the follicular fluids (Valckx et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…We found that the fertilization rate and implantation rate in overweight and obese PCOS patients were not significantly different from those of the normal weight patients. As obesity is a state of chronic inflammation and metabolic disorder, markers of inflammation and oxidative stress are increased in the serum and ovarian follicular fluids (Merhi et al, 2015;Buyuk et al, 2017), which may have a negative impact on the IVF outcomes (Cakiroglu et al, 2016). The aberrant serum metabolic changes, such as the increased cholesterol, triglycerides, and apolipoprotein A, were often observed in obesity, which were usually reflected in the follicular fluids (Valckx et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…4 This local injury induces the expression of several pro-inflammatory cytokines and chemokines, such as tumour necrosis factor alpha (TNF-α) and growth-regulated oncogene alpha (GRO-α). 6,7 It is critical that the local immune environment be tightly regulated for implantation to occur, and one potential contributing factor to an altered immune environment in humans is chronic endometritis, a condition estimated to affect approximately 10% of women. 6,7 It is critical that the local immune environment be tightly regulated for implantation to occur, and one potential contributing factor to an altered immune environment in humans is chronic endometritis, a condition estimated to affect approximately 10% of women.…”
mentioning
confidence: 99%
“…5 However, cytokine and chemokine expression must be precisely regulated, as inappropriately elevated concentrations of certain cytokines and chemokines are associated with implantation failure. 6,7 It is critical that the local immune environment be tightly regulated for implantation to occur, and one potential contributing factor to an altered immune environment in humans is chronic endometritis, a condition estimated to affect approximately 10% of women. 8,9 Chronic endometritis refers to inflammation of the endometrium and is often caused by gram-negative bacterial strains such as Escherichia coli and Gardnerella vaginalis or by Ureaplasma urealyticum and Mycoplasma species.…”
mentioning
confidence: 99%
“…This ovarian dysfunction was not observed in MCP-1 knockout mice that became obese following ingestion of a high-fat diet, suggesting that lack of MCP-1 may be protective against high-fat- and obesity-induced ovarian dysfunction. Further supporting this hypothesis, we showed that elevated serum MCP-1 levels were associated with poorer outcome in women undergoing IVF [ 140 ], an effect that is pronounced in women with already diminished ovarian reserve. Additionally, AGE levels in follicular fluid were negatively correlated with IVF outcome parameters: fewer oocytes retrieved and fertilized, fewer embryos and lower ongoing pregnancy rate [ 137 ].…”
Section: Introductionmentioning
confidence: 70%